Embedding systematic quality assessments in supportive supervision at primary healthcare level: application of an electronic Tool to Improve Quality of Healthcare in Tanzania. Issue 1 (December 2016) - Mboya, Dominick; Mshana, Christopher; Kessy, Flora; Alba, Sandra; Lengeler, Christian; Renggli, Sabine; Vander Plaetse, Bart; Mohamed, Mohamed; Schulze, Alexander
Abstract Background Assessing quality of health services, for example through supportive supervision, is essential for strengthening healthcare delivery. Most systematic health facility assessment mechanisms, however, are not suitable for routine supervision. The objective of this study is to describe a quality assessment methodology using an electronic format that can be embedded in supervision activities and conducted by council health staff. Methods An electronic Tool to Improve Quality of Healthcare (e-TIQH) was developed to assess the quality of primary healthcare provision. The e-TIQH contains six sub-tools, each covering one quality dimension: infrastructure and equipment of the facility, its management and administration, job expectations, clinical skills of the staff, staff motivation and client satisfaction. As part of supportive supervision, council health staff conduct quality assessments in all primary healthcare facilities in a given council, including observation of clinical consultations and exit interviews with clients. Using a hand-held device, assessors enter data and view results in real time through automated data analysis, permitting immediate feedback to health workers. Based on the results, quality gaps and potential measures to address them are jointly discussed and actions plans developed. Results For illustrative purposes, preliminary findings from e-TIQH application are presented from eight councils of Tanzania for the period 2011–2013, with a quality score <75 % classed as 'unsatisfactory'. Staff motivation (<50 % in all councils) and job expectations (≤50 %) scored lowest of all quality dimensions at baseline. Clinical practice was unsatisfactory in six councils, with more mixed results for availability of infrastructure and equipment, and for administration and management. In contrast, client satisfaction scored surprisingly high. Over time, each council showed a significant overall increase of 3–7 % in mean score, with the most pronounced improvements in staff motivation and job expectations. Conclusions Given its comprehensiveness, convenient handling and automated statistical reports, e-TIQH enables council health staff to conduct systematic quality assessments. Therefore e-TIQH may not only contribute to objectively identifying quality gaps, but also to more evidence-based supervision. E-TIQH also provides important information for resource planning. Institutional and financial challenges for implementing e-TIQH on a broader scale need to be addressed.